CALVING PATTERN IN KANKREJ CATTLE AND MEHSANA BUFFALO AT AN ORGANIZED FARM IN NORTH GUJARAT - PATEL, MP; PAREEK, NK; ANKUYA, KJ; RATHOD, BS; PRAJAPATI, KB (The Indian Journal of Animal Reproduction, 2016)
The seasonality in calving pattern at an organized farm in North Gujarat was recorded to present statistics on regional trends for calving pattern. For assessing the seasonality of calving patterns, the data on 821 Kankrej cattle and 486 Mehsana buffalo (calving between 2006 and 2015) maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat was considered. The month and season had impact (p<0.05) on calving pattern in Mehsana buffalo and Kankrej cattle. The highest calving for Kankrej and Mehsana was in summer (33.99%) and rainy (38.69%) season, respectively. The lowest calving for Kankrej and Mehsana was in autumn (18.03%) and summer (5.34%) season, respectively. The seasonality of calving was 0.63 and 0.95 for Kankrej cattle and Mehsana buffalo, respectively. In brief, Mehsana buffalo had distinct seasonal variation in calving pattern as compared to Kankrej cattle at an organized farm in North Gujarat.